Analysis of Metacognitive Awareness, Learning Methods, and Learning Outcomes in Biology of Student - Dian Intan Rahmadhni; Moralita Chatri (Postgraduate, University of Mataram, 2023)
This study aimed to determine the relationship between metacognition awareness, learning methods and learning outcomes in biology based on the academic abilities of students in class X MIPA at SMA Negeri Bangkinang city for the Academic Year 2022/2023. This research was conducted on January 9 - January 17, 2023. This research was a correlational study and data collection used questionnaires, documentation and interviews. The sample in this study were 218 students with different levels of academic ability. Data analysis in this study used the Person Product Moment correlation analysis technique. The results showed that at high academic levels, metacognition awareness (X1), learning methods (X2) and learning outcomes (Y) had a moderate relationship (0.418). In low academic metacognition awareness (X1), learning methods (X2) and learning outcomes (Y) there is a moderate relationship (0.447). For significant test scores obtained at high academic, metacognition awareness (X1), ways of learning (X2) and learning outcomes (Y) t-test (4.75) > t-table (1.98). At low academic levels, metacognition awareness (X1), learning methods (X2) and learning outcomes (Y) t-test (5.16) > t-table (1.98). The results showed that there was a significant relationship between metagonistic awareness, ways of learning and learning outcomes in biology based on the academic abilities of class X students at SMA Negeri Bangkinang city